Students' Information Processing Abilities and Cognitive Processes in Biotechnology Learning - Yusnita Renata Tamba; Adi Rahmat; Rini Solihat (Postgraduate, University of Mataram, 2023)
The learning outcomes in the independent curriculum expect students to have skills in processing and analyzing data and information. These skills are in line with the information processing abilities developed by Marzano (1993). This research aims to determine the level of students' information processing abilities in biotechnology learning and its relationship with students' cognitive processes. The data in this research were processed using PLS-SEM (Partial Least Square–Structural Equation Model) analysis. Based on the results of the analysis, the instruments used to test information processing abilities, level 1 retrieval and level 2 comprehension cognitive systems, metacognitive systems and self-systems are valid and reliable. However, the level 3 analysis and level 4 knowledge utilization cognitive systems showed invalid and unreliable results so no further evaluation was carried out at these two levels. The results of the inner model analysis show that increasing information processing abilities have a significant and linear relationship to increasing cognitive processes. The relationship between information processing abilities and cognitive processes from the highest respectively is students' comprehension (L2), self-system (L6), metacognitive system (L5), and retrieval (L1).